PRODUKTIVITAS DAN RENDEMEN PEMBUATAN ANYAMAN PANDAN LAUT (Pandanus odorifer) SERTA KONTRIBUSI TERHADAP PENDAPATAN DI DESA PULAU KERAYAAN - Rezky Ramadhan; Noor Mirad Sari; Yuniarti Yuniarti (Jurnal Sylva Scienteae, 2024)
The purpose of this study was to determine the average value of the contribution of woven sea pandanus to productivity, yield, and income in the form of fans, hoods, and bowls. Analyze the data collected by collecting information on the contribution of income to productivity, yield, and productivity of the woven sea pandanus craftsmen. Findings show that fan mats produce an average of 0.075 pieces per hour. The hood productivity averaged 0.042 pieces per hour. The average woven bowl productivity is 0.031 pieces per hour. The average yield of woven fans was 76.12 percent, the average yield of hoods was 71.59 percent, and the average yield of woven bowls was 57.38 percent. For weaving fans, the average net income value per year was IDR 2,886,118, with an average of IDR. Bowl weaving generated an annual net income of IDR 2,824,844. Bowl, hoods, and fan contributions all had average values of 29.03 percent and 29.06 percent, respectively. The highest average value of woven productivity was 0.075 pieces per hour, the highest average yield was 76.12 percent, and the highest annual average net income was IDR 2,886,118, with fan weaving contributing 30.06 percent of the highest average contribution valueTujuan dari penelitian ini adalah untuk mengetahui nilai rata-rata kontribusi anyaman pandan laut terhadap produktivitas, hasil, dan pendapatan berupa kipas, tudung, dan mangkok.  Analisis data yang dikumpulkan melalui pengumpulan informasi mengenai kontribusi pendapatan terhadap produktivitas, hasil, dan produktivitas pengrajin anyaman pandan laut. Temuan menunjukkan bahwa tikar kipas menghasilkan rata-rata 0,075 lembar per jam. Produktivitas kap mesin rata-rata 0,042 lembar per jam. Produktivitas mangkuk anyaman rata-rata 0,031 lembar per jam. Hasil rata-rata kipas tenun adalah 76,12 persen, rendemen rata-rata tudung 71,59 persen, dan rendemen rata-rata anyaman mangkok 57,38 persen. Untuk kipas tenun, rata-rata nilai pendapatan bersih per tahun adalah Rp2.886.118, dengan rata-rata Rp. Anyaman mangkok menghasilkan pendapatan bersih tahunan Rp2.824.844.2.741.760.Mangkok, tudung, dan kipas tenun kontribusi semuanya memiliki nilai rata-rata masing-masing 29,03 persen dan 29,06 persen. Nilai rata-rata produktivitas anyaman tertinggi adalah 0,075 lembar per jam, hasil rata-rata tertinggi 76,12 persen, dan pendapatan bersih rata-rata tahunan tertinggi sebesar Rp2.886.118, dengan tenun kipas menyumbang 30,06% dari nilai kontribusi rata-rata tertinggi.